2016
DOI: 10.1371/journal.pone.0165552
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Population Structure of the Coral Reef Sea Star Linckia laevigata in the Western Indian Ocean and Indo-West Pacific

Abstract: The coral reef sea star Linckia laevigata is common on shallow water coral reefs of the Indo-West Pacific. Its large geographic distribution and comprehensive data from previous studies makes it suitable to examine genetic differentiation and connectivity over large geographical scales. Based on partial sequences of the mitochondrial cytochrome oxidase I (COI) gene this study investigates the genetic population structure and connectivity of L. laevigata in the Western Indian Ocean (WIO) and compares it to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 68 publications
(93 reference statements)
5
26
2
Order By: Relevance
“…This is a main limitation to draw general conclusions when comparing patterns of genetic structure that can only be resolved through better coordination among research groups. Our results are in agreement with previous studies and suggest that genetic exchange among eastern and western Indian Ocean might be limited by the presence of only a few islands that could facilitate connectivity via island hopping (Otwoma & Kochzius, ; Sheppard et al, ). The Maldives seems to be one of these important crossroads where different lineages meet.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is a main limitation to draw general conclusions when comparing patterns of genetic structure that can only be resolved through better coordination among research groups. Our results are in agreement with previous studies and suggest that genetic exchange among eastern and western Indian Ocean might be limited by the presence of only a few islands that could facilitate connectivity via island hopping (Otwoma & Kochzius, ; Sheppard et al, ). The Maldives seems to be one of these important crossroads where different lineages meet.…”
Section: Discussionsupporting
confidence: 94%
“…We found that there is a significant congruence of patterns of genetic differentiation among species and that the Maldives (western/central Indian Ocean) represents a location of overlap or possible hybridization among distinct anemone populations or lineages (Sheppard et al, ). Previous studies have reported genetic discontinuity between the eastern and western Indian Ocean in different taxa including coral reef fishes (Bay, Choat, van Herwerden, & Robertson, ; Gaither et al, ; Huyghe & Kochzius, ; Leray et al, ) and invertebrates such as echinoderms (Otwoma & Kochzius, ; Vogler et al, ) and giant clams (Hui et al, ). Only one of these included samples from the Maldives (Vogler et al, ) and did not report overlap of different clades at these islands.…”
Section: Discussionmentioning
confidence: 99%
“…It also receives waters from the East African Coastal Current along coastal Tanzania and Kenya. Water from the South Equatorial Current enters the northern Mozambique Channel, forming a series of eddies which propagate southwards through the channel (Halo et al, ; Otwoma & Kochzius, ). These waters are augmented by eddies originating from the East Madagascar Current at the southern end of the channel (de Ruijter et al, ; Ridderinkhof, Bars, Heydt, & Ruijter, ), and their confluence forms the upper Agulhas Current off southern Mozambique and eastern South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…It also receives waters from the East African Coastal Current along coastal Tanzania and Kenya. Water from the South Equatorial Current enters the northern Mozambique Channel, forming a series of eddies which propagate southwards through the channel (Halo et al, 2017;Otwoma & Kochzius, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our EBSP results together with Tajima's D indicate population expansions for most of the studied species (Appendix S9). Expansions were also suggested for honeycomb grouper (Muths et al., ), humbug damselfish (Liu et al., ), blue sea star (Otwoma & Kochzius, ), using mismatch distribution and/or Harpending's R analyses, and for threadfin butterflyfish (DiBattista et al., ) and whitecheek surgeonfish (DiBattista et al., ) by directly estimating the time of expansions. Although the general signal for expansion can be taken as a support for Survival (Table ), locations of population expansions are inconsistent across species.…”
Section: Discussionmentioning
confidence: 99%